2022
DOI: 10.3390/su14063333
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Potential Function of Prokaryotic and Eukaryotic Communities from Different Mangrove Sediments

Abstract: Mangrove trees generally play important roles in protecting intertidal ecosystems. The mangrove root-associated sediments provide a repertoire of microbial communities that contribute to pivotal ecological functions in the system. In the present study, we used the high-throughput sequencing and PICRUSt-predicted functional information (based on 16S/18S rDNA profiles) to investigate the bacterial, archaeal, and fungal communities in two mangrove systems, located in the estuary of the Jiulong River (China), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
(66 reference statements)
2
2
0
Order By: Relevance
“…By linking microbial abundances to their utilization of carbon substrates along a large‐scale temperature gradient, our study suggests climate warming will reduce carbon sequestration in lakes. Consistent with others (Bowd et al, 2022; Hu et al, 2020; Li, Zhang, et al, 2022; Zhang, Gui, et al, 2022), we found that warming temperature could inhibit the abundance of Proteobacteria but promote the abundance of Cyanobacteria and Actinobacteriota. Cyanobacteria in particular tend to be temperature‐limited and can release bioavailable lipids and amino acids into freshwaters when temperature constrains are removed (Liu et al, 2020; Wagner et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…By linking microbial abundances to their utilization of carbon substrates along a large‐scale temperature gradient, our study suggests climate warming will reduce carbon sequestration in lakes. Consistent with others (Bowd et al, 2022; Hu et al, 2020; Li, Zhang, et al, 2022; Zhang, Gui, et al, 2022), we found that warming temperature could inhibit the abundance of Proteobacteria but promote the abundance of Cyanobacteria and Actinobacteriota. Cyanobacteria in particular tend to be temperature‐limited and can release bioavailable lipids and amino acids into freshwaters when temperature constrains are removed (Liu et al, 2020; Wagner et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…However, metabolic activities toward oxidation of nitrogen compounds only involved nmo genes by Lokiarchaeum sp. (Figure 5B), potentially resulting in minor production of nitrite (Zhang et al, 2022). Consistent with the apparent lack of metabolic expression by anammoxrelated Planctomycetota (Figure 3C), we did not detect any ORF related to hydrazine (i.e., H 2 N 4 ) oxidoreductase (hzo) in shallow sediment (Kong et al, 2013).…”
Section: Ammonification and Denitrification In Sulfidic Sedimentsupporting
confidence: 82%
“…Recently, some researchers proposed to cluster these families into a phylum named Desulfobaterota [ 49 , 50 ]. The Anaerolineaceae family are anaerobic bacteria found in the upper zones of mangrove sediments that play a role in nitrate reduction to ammonium [ 51 ]. In preserved and recovery zones, we observed a high abundance of Thioalkalispiraceae, which are chemolithoautotrophic bacteria able to oxidize sulfur compounds and that have been obtained from soda lakes, hypersaline lakes, or marine environments, with specific NaCl concentration requirements for growth [ 52 ].…”
Section: Discussionmentioning
confidence: 99%